Absorção e níveis críticos de fósforo na parte aérea da mamoneira cultivada em diferentes classes de solos - Brito Neto, Jose Felix de; Büll, Leonardo Theodoro [UNESP]; Macedo Beltrao, Napoleao Esberard de; Rigon, Joao Paulo Gonsiorkiewicz [UNESP]; Sofiatti, Valdinei (Univ Estadual Londrina, 2014)
Soil that has a high degree of weathering, with more inorganic P bound to Fe and Al oxides, has less P availability to plants. Thus, the critical element of a plant refers to the level below which the growth rate and plant production decreases, demonstrating the need for supplementary fertilization. Accordingly, an experiment was conducted in a greenhouse at Embrapa Algodao with the objective of evaluating the response of castor plants to five doses of P in four types of soil with different adsorption characteristics and critical levels of foliar P. The experimental design was completely randomized in a 4 x 5 factorial design, four types of soil and 5 levels of P with four replications. For TCo, there was an increase in height growth, with dose of 229.6 mg dm(-3) responsible for maximum plant height (74.3 cm). The largest diameter stem (17.58 mm) was observed in CXve with an application of 229.6 mg dm(-3) of P; a decrease was seen when using higher doses. The increase in leaf area was smaller in RY (4724.8 cm(2)), where it was obtained with a dose of 280.2 mg dm(-3). In general, critical levels of P in the plant shoots did not vary much between the soils. The critical level of P in castor bean shoot dry mass was higher (4.61 g kg(-1)) in TCo, this result being directly related to the low clay content of the soil.
Absorption and critical levels of phosphorus in castor bean shoots grown in different soil classes
Keywords: Availability; plants; phosphorus; castor bean